2010
DOI: 10.2139/ssrn.1541707
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of, and the Relationship Between FDI and Economic Growth in Bangladesh

Abstract: Inward FDI to the middle-income countries has the evidence as a major stimulus to the economic growth; conventionally at export-oriented manufacturing sector. In point of fact, basic macro fundamentals like as growth of gross domestic capital formation, foreign reserve, infrastructure etc.accelerates the FDI inflows. This study reviews the long-run trend on the time scale of FDI to Bangladesh over the period 1975-2006 and major factors determining foreign companies' decisions to invest, in associated with econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
3
11
1
Order By: Relevance
“…The nexus between FDI-led economic growth of Bangladesh attract researchers of exploring their fundamental relationship. In the empirical literature, we observed that the positive effects of FDI on the economic growth of Bangladesh confirmed by different researchers see for an instance, (Bari, 2013;Hussain & Haque, 2016;Adhikary, 2011;Ahamed & Tanin, 2010). The growth of FDI inflows in Bangladesh is maintaining at a stable rate of 5.11% in the year of 2018 from the prior year 2017.…”
Section: Introduction 12supporting
confidence: 68%
“…The nexus between FDI-led economic growth of Bangladesh attract researchers of exploring their fundamental relationship. In the empirical literature, we observed that the positive effects of FDI on the economic growth of Bangladesh confirmed by different researchers see for an instance, (Bari, 2013;Hussain & Haque, 2016;Adhikary, 2011;Ahamed & Tanin, 2010). The growth of FDI inflows in Bangladesh is maintaining at a stable rate of 5.11% in the year of 2018 from the prior year 2017.…”
Section: Introduction 12supporting
confidence: 68%
“…Positive association between FDI and GDP growth where FDI can enhance economic growth has been investigated after doing a range of studies by Shaari, Hong and Shukeri (2012) According to Ahamad and Tanin (2010), gradually increased FDI in recent years has had positive influence on the economic progress of Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other way round could be that, the growth of GDP could be the reason for increasing value of FDI rather than FDI promotes GDP. However, Ahamad and Tanin (2010) investigated the relationship between FDI and GDP empirically in the context of Bangladesh by analyzing time series data of 1970-2006 and therefore revealed economic growth attracted FDI inflow instead FDI generates economic growth. The same sort of point agreed by Ghali & Al-Mutawa (1999), Levine and Renelt (1992), and , Adhikary and Mengistu (2008) that domestic investment can raise economic growth and FDI as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the researcher's works with determinants of economic growth in Bangladesh like Ahamed and Tanin (2010) explored that FDI is an important determinant of economic growth for Bangladesh. Sultan (2008) shows export, import, and industry value added are important factors for growth.…”
Section: The Economics and Finance Lettersmentioning
confidence: 99%